2020
DOI: 10.1021/acssuschemeng.0c01814
|View full text |Cite
|
Sign up to set email alerts
|

In situ Grown Ni phosphate@Ni12P5 Nanorod Arrays as a Unique Core–Shell Architecture: Competitive Bifunctional Electrocatalysts for Urea Electrolysis at Large Current Densities

Abstract: It is still a big challenge to develop active, stable, and easy-to-make bifunctional non-noble electrocatalysts for upshifting overall urea-assisted water splitting toward practical environmental applications at large current densities with lower cell voltages. In response, here we report a competitive bifunctional electrocatalyst that can catalyze both the urea oxidation reaction (UOR) and hydrogen evolution reaction (HER) by fabricating the in situ grown Ni phosphate (shell)-anchored Ni12P5 nanorod (core) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…6 Generally speaking, the water electrolysis strategy is one of the most efficient ways to produce hydrogen energy, which is composed of the anodic oxygen evolution reaction (OER) and cathodic hydrogen evolution reaction (HER) [7][8][9][10] and is sought aer and loved by many researchers. 11,12 However, as the most important half-reaction of the anode of water electrolysis, oxygen evolution reaction (OER) has sluggish kinetics and is complicated by a four-electron transferring process (4OH À / 2H 2 O + O 2 + 4e À ), which seriously hinders the conversion and application of hydrogen energy process. 13 The urea oxidation reaction (UOR), which was also an anode reaction, has a 6-electron transmission process (CO(NH 2 ) 2 + 6OH À / N 2 + 5H 2 O + CO 2 + 6e À ).…”
Section: Introductionmentioning
confidence: 99%
“…6 Generally speaking, the water electrolysis strategy is one of the most efficient ways to produce hydrogen energy, which is composed of the anodic oxygen evolution reaction (OER) and cathodic hydrogen evolution reaction (HER) [7][8][9][10] and is sought aer and loved by many researchers. 11,12 However, as the most important half-reaction of the anode of water electrolysis, oxygen evolution reaction (OER) has sluggish kinetics and is complicated by a four-electron transferring process (4OH À / 2H 2 O + O 2 + 4e À ), which seriously hinders the conversion and application of hydrogen energy process. 13 The urea oxidation reaction (UOR), which was also an anode reaction, has a 6-electron transmission process (CO(NH 2 ) 2 + 6OH À / N 2 + 5H 2 O + CO 2 + 6e À ).…”
Section: Introductionmentioning
confidence: 99%
“…Since some Ni-based materials also have good HER catalytic behaviors, they were successfully applied in overall urea electrocatalysis for concurrent H 2 production, spanning from oxide, [11] hydroxide, [12] sulfide, [13] selenide, [14] and phosphide. [15,16] Despite of the current development of the catalysts for overall urea electrolysis, the breakthroughs are expected to be successfully addressed for exploring new catalysts with high performance toward real application. Considering the potential for the oxidation of Co 2 + to Co 3 + is lower than that of Ni 2 + to Ni 3 + , the Co-based materials are more likely favorable for UOR electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that nickel‐based materials can be electrochemically oxidized to generate Ni 3+ ions as the active centers for a following chemical oxidation of urea, [9,10] hence, great endeavors have been devoted in pursuit of various Ni‐based catalysts for effective UOR electrolysis. Since some Ni‐based materials also have good HER catalytic behaviors, they were successfully applied in overall urea electrocatalysis for concurrent H 2 production, spanning from oxide, [11] hydroxide, [12] sulfide, [13] selenide, [14] and phosphide [15,16] …”
Section: Introductionmentioning
confidence: 99%
“…Though numerous photocatalytic systems have been reported for overall water splitting, solar-to-hydrogen (STH) efficiencies of powder photocatalytic and photoelectrochemical systems using earth abundant materials remain below ≈5%. [315,316] To a large extent this is due to the [285] 2D Ni-MOF nanosheets, [281] Ni 2 P NF/CC, [295] HS-Ni 2 P/ Ni 0.96 S/NF, [293] Ni(OH) 2 -nanomeshs, [296] NiIr-MOF/NF, [297] NiTe-Ni(OH) 2 , [292] P-CoS 2 /Ti, [298] Ni(OH) 2 nanoflakes, [299] RuO 2 , [300] Ni/Co, [301] NiClO-D, [284] NF/NiMo-Ar, [289] CoMn/CoMn 2 O 4 , [291] (Ni-WO 2 )@C/NF, [302] Ni-NiO-Mo 0.84 Ni 0.16 , IrO 2 , [293] Ni 12 P 5 /Ni-Pi/NF, [300] Ni/C, [303] NF-NiMoO-H 2 , [289] Pt/C. [289] Detailed information about experimental conditions are summarized in Table S14 of the Supporting Information.…”
Section: Hydrogen Production By Solar-driven Organic Transformationmentioning
confidence: 99%